Disrupted Diurnal Oscillation of Gut-Derived Short Chain Fatty Acids in Shift Workers Drinking Alcohol: Possible Mechanism for Loss of Resiliency of Intestinal Barrier in Disrupted Circadian Host - Swanson, Garth R. (Transl Res, 2020)
Microbiota derived short chain fatty acids (SCFAs) are produced by fermentation of non-digestible fiber, and are a key component in intestinal barrier homeostasis. Since the microbiome has diurnal fluctuations, we hypothesized that SCFAs in humans have a diurnal rhythm and their rhythmicity would be impacted by the host central circadian misalignment (night shift work) which would make intestinal barrier more susceptible to disruption by alcohol. To test this hypothesis, we studied three groups of subjects: patients with alcohol use disorder, but no liver disease (AD), healthy day workers (DW), and night workers (NW). All subjects were studied at baseline and then in DW and NW subjects after moderate daily alcohol (0.5 g/kg) for seven days. Gut derived plasma SCFAs showed a significant circadian oscillation by cosinor analysis in DW; however, SCFA in the AD and NW subjects lost 24 hour rhythmicity. Decrease in SCFA correlated with increased colonic permeability. Both chronic and moderate alcohol consumption for one week caused circadian disruption based on wrist actigraphy and urinary melatonin. Our study shows that: (1) gut derived plasma SCFAs have a diurnal rhythm in humans that is impacted by the central clock of the host; (2) moderate alcohol suppresses SCFAs which was associated with increased colonic permeability; and (3) less invasive urinary 6-SM correlated and rest-activity actigraphy correlated with plasma melatonin. Future studies are needed to examine the role circadian misalignment on gut derived SCFAs as possible mechanism for loss of intestinal barrier resiliency to injurious agents like alcohol.